2014
DOI: 10.1089/ars.2013.5236
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase 7 Utilizes Hydrogen Peroxide Generated by Ero1α to Promote Oxidative Protein Folding

Abstract: Aims: Ero1 flavoproteins catalyze oxidative folding in the endoplasmic reticulum (ER), consuming oxygen and generating hydrogen peroxide (H 2 O 2 ). The ER-localized glutathione peroxidase 7 (GPx7) shows protein disulfide isomerase (PDI)-dependent peroxidase activity in vitro. Our work aims at identifying the physiological role of GPx7 in the Ero1a/PDI oxidative folding pathway and at dissecting the reaction mechanisms of GPx7. Results: Our data show that GPx7 can utilize Ero1a-produced H 2 O 2 to accelerate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 39 publications
2
96
0
Order By: Relevance
“…To further confirm that GPX‐6 in C. elegans and GPx7 in human share functional similarities, we purified both proteins and measured their peroxidase activities by in vitro NADPH consumption assays. A unique feature of human GPx7 is that it uses H 2 O 2 to oxidize the ER‐localized protein disulfide isomerase (PDI) rather than glutathione itself (Nguyen et al., 2011; Wang et al., 2014). Like human GPx7, C. elegans GPX‐6 did not display any glutathione peroxidase activity but had greatly increased peroxidase activity when PDI was used as a substrate (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further confirm that GPX‐6 in C. elegans and GPx7 in human share functional similarities, we purified both proteins and measured their peroxidase activities by in vitro NADPH consumption assays. A unique feature of human GPx7 is that it uses H 2 O 2 to oxidize the ER‐localized protein disulfide isomerase (PDI) rather than glutathione itself (Nguyen et al., 2011; Wang et al., 2014). Like human GPx7, C. elegans GPX‐6 did not display any glutathione peroxidase activity but had greatly increased peroxidase activity when PDI was used as a substrate (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…Mature human GPx7 and C. elegans GPX‐6 proteins including an N‐terminal 6× His tag were purified with a nickel‐chelating column (GE Healthcare), and peroxidase activity was conducted as previously described (Wang et al., 2014). In brief, the decrease in absorbance at 340 nm due to NADPH (150 μ m ; Roche) consumption by glutathione reductase (0.24 U; Sigma) was monitored, in the presence of 150 μ m H 2 O 2 , 0.5 m m GSH (Sigma), and 10 μ m human PDI, with or without 10 μ m human GPx7 or C. elegans GPX‐6, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes transfer electrons from glutathione [33], protein thiols [128] or PDI [33,127] to hydrogen peroxide. The source of thiol-oxidizing hydrogen peroxide can be the Ero1-catalyzed reaction [32,127]. However, it was also observed that Ero1-independent luminal hydrogen peroxide generation -via gulonolactone oxidase activity -could also stimulate disulfide bond formation [45].…”
Section: Formation and Elimination Of Hydrogen Peroxide In The Ermentioning
confidence: 99%
“…This enzyme family is represented by GPx7 and 8 in the ER lumen, which have been proved to be effective PDI peroxidases (i.e. they can use reduced PDI instead of GSH as electron donor) [30][31][32]. However, at least in case of Gpx7, GSH can be an alternative substrate in the reaction, with a relatively low rate [33].…”
mentioning
confidence: 99%